2002
DOI: 10.1159/000048206
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prolactin-Releasing Peptide on Tuberoinfundibular Dopaminergic Neuronal Activity and Prolactin Secretion in Estrogen-Treated Female Rats

Abstract: Both systemic and central effects of a newly discovered prolactin (PRL)-releasing factor (PRF), prolactin-releasing peptide (PrRP), were determined in this study. Systemic injection of PrRP (1 and 10 µg/rat, i.v.) stimulated PRL secretion in ovariectomized, estrogen-treated rats similar to the effect of another PRF, thyrotropin-releasing hormone (TRH). Pretreatment with a dopamine D2 receptor antagonist, sulpiride (1 µg/rat, i.v.), potentiated the stimulatory effect of both PrRP and TRH on PRL secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…ICV PrRP did not increase peripheral PRL concentrations in rats (Samson et al 2003) or sheep (Curlewis et al 2002). In rats, the PrRP receptor is expressed abundantly in the anterior pituitary (Roland et al 1999), and the effect of PrRP on stimulation of PRL release was reported both in vitro and in vivo (Hinuma et al 1998;Matsumoto et al 1999;Yuan et al 2002). PrRP was previously shown to stimulate PRL secretion from anterior pituitary cell cultures of rats (Hinuma et al 1998) and sheep, although the response was very weak in sheep (Curlewis et al 2002).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…ICV PrRP did not increase peripheral PRL concentrations in rats (Samson et al 2003) or sheep (Curlewis et al 2002). In rats, the PrRP receptor is expressed abundantly in the anterior pituitary (Roland et al 1999), and the effect of PrRP on stimulation of PRL release was reported both in vitro and in vivo (Hinuma et al 1998;Matsumoto et al 1999;Yuan et al 2002). PrRP was previously shown to stimulate PRL secretion from anterior pituitary cell cultures of rats (Hinuma et al 1998) and sheep, although the response was very weak in sheep (Curlewis et al 2002).…”
Section: Discussionmentioning
confidence: 86%
“…PrRP was previously shown to stimulate PRL secretion from anterior pituitary cell cultures of rats (Hinuma et al 1998) and sheep, although the response was very weak in sheep (Curlewis et al 2002). Intravenously administered PrRP was also shown to increase plasma PRL concentration in rats (Matsumoto et al 1999;Yuan et al 2002) but not in sheep (Curlewis et al 2002). These evidences suggest that PrRP might regulate PRL release from the anterior pituitary in rats which is still debatable, and that PrRP is unlikely to be an important regulator of PRL release in sheep.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Although many candidates have been proposed, none fulfils all the required criteria. Yuan et al [21] reported that a newly discovered candidate, prolactin-releasing peptide (PrRP), stimulates prolactin secretion in ovariectomized, estrogen-treated rats. The blockade of dopamine D 2 receptors potentiates this stimulatory action.…”
mentioning
confidence: 99%